(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2023)
Background: Vulvar malignancies are the fourth commonest of genital malignancies. The sarcoma type is associated with neurofibromatosis disease. Case presentation: A 29-year-old nulliparous presented to the outpatient gynecological clinic with a five-year history of a recurrent right vulvar mass. The mass was initially excised without histological analysis. Histological examination of a reexcised mass diagnosed a spindle cell sarcoma. She was then lost to follow-up for one year. The mass recurred and she received external beam radiation. On admission, she was in good general status with generalized café au lait spots and neurofibromas. Perineal examination revealed an ulcerated right vulvar mass. Toilet vulvectomy and diversion colostomy were performed followed by chemotherapy. She was discharged after five months with a well-granulated wound. Colostomy was reversed six months later. Conclusion: Vulvar sarcoma is a rare vulvar malignancy type usually associated with neurofibromatosis. This case highlights the missed opportunities in its management. A high suspicion threshold is critical for early diagnosis and management to curb the morbidity and mortality rate.